Peran Influencer Dalam Proses Electornic Word Of Mouth (E- Wom) Dalam Meningkatan Brand Image - Shinta Abdul Rahman; Qolbiyah Qolbiyah; Sariya Sileuw (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
For a long time, Word of Mouth (EWOM) has been considered the main source of information that influences consumer decisions. In the era of globalization, EWOM has developed into a broader, albeit more personal, form, known as electronic word of mouth (EWOM). Advances in electronic systems and the emergence of social media platforms, for example Instagram, open up new and promising potential for the evolution of EWOM as an integral part of business advertising/business promotion strategies. When EWOM regarding a product receives a positive response, the impact has a direct impact on the brand image or good brand image. One of the related concepts in the formation of EWOM and brand image on Instagram today is the role of influencers. The aim of this research is to understand the role of social media influencers in shaping positive EWOM and how this impacts improving brand image. Qualitative methods were applied in this research by collecting data through journals, books and articles. The findings from this research show that influencers who have a high level of trust have a very influential role in forming EWOM which provides positive EWOM reviews regarding the products being marketed. This positive opinion from EWOM directly increases the positive value of the brand image in society, which shows that the success of influencers can help audiences understand information about products and increase their desire to make purchases.